PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2022-2024 - Ramot Benedictus Situmorang; Robinhot Gultom; Rintan Saragih (STKIP Subang, 2026)
This study aims to examine and analyse the effect of Ownership Structure, proxied by Institutional Ownership (IO), and Leverage, Proxied by Debt to Equity Ratio (DER), and Profitability, proxied by Return on Assets (ROA), on Firm Value, proxied by Price to Book Value (PBV), in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The population in this study consisted of 92 companies, with a sample of 35 companies selected using purposive sampling. The data analysis method used was multiple linear regression analysis. The results showed that, partially, the variables of Ownership Structure, Leverage, and Profitability had a positive and significant effect on Company Value. Simultaneously, the three independent variables also had positive and significant effect on Company Value. The coefficient of determination test results show that KI, DER, and ROA are able to explain 98,9% of the variation in Company Value, while the remaining 1,1% is influenced by other variables outside the research model